Pengaruh rasio profitabilitas dan likuiditas dengan struktur modal sebagai variabel intervening terhadap nilai perusahaan - Erikawati, Civi; Saputra, Riyan Abdurrahman (Nur Science Institute, 2023)
The purpose of this study is to analyze and obtain empirical evidence of the effect of profitability ratios, liquidity on firm value, the effect of capital structure on firm value, effect of profitability on capital structure, the effect liquidity on capital structure, and capital structure can mediate the influence of profitability and liquidity on value company. The data collection technique is through literature study and non-participant observation, namely by collecting, recording, and reviewing secondary data in the form of financial statements of manufacturing companies on the Indonesia stock exchange. The population in this study are companies listed on the Indonesia Stock Exchange during 2017-2019. Determination of the sample using a purposive sampling method. The data analysis method used multiple linear regression. The results of this study are that variable ROI has no significant effect on capital structure, while variable current ratio does not affect capital structure. Variable ROI has a significant effect on firm value. Meanwhile, a variable capital structure can significantly affect firm value.